Experimental study on the 4H-SiC-based VDMOSFETs with lightly doped P-well field-limiting rings termination. (March 2017) - He, Yan Jing; Lv, Hong Liang; Tang, Xiao Yan; Song, Qing Wen; Zhang, Yi Meng; Han, Chao; Zhang, Yi Men; Zhang, Yu Ming
Highlights: Lightly doped P-well FLRs on 4H-SiC VDMOSFETs were optimized and fabricated. The P-well FLRs possess lower interface damage in the termination region. The P-well FLRs achieve 90% of the plane parallel breakdown voltage. Abstract: A lightly doped P-well field-limiting rings (FLRs) termination on 4H-SiC vertical double-implanted metal-oxide-semiconductor field-effect transistors (VDMOSFETs) has been investigated. Based on the simulation, the proposed termination applied to 4H-SiC VDMOSFET could achieve an almost same breakdown voltage (BV) and have the advantage of lower ion-implantation damage comparing with P + FLRs termination. Meanwhile, this kind of termination also reduces the difficulty and consumption of fabrication process. 4H-SiC VDMOSFETs with lightly doped P-well (FLRs) termination have been fabricated on 10 μm thick epi-layer with nitrogen doping concentration of 6.2 × 10 15  cm −3 . The maximum breakdown voltage of the 4H-SiC VDMOSFETs has achieved as high as 1610 V at a current of 15 μA, which is very close to the simulated result of 1643 V and about 90% of the plane parallel breakdown voltage of 1780 V. It is considered that P-well FLRs termination is an effective, robust and process-tolerant termination structure suitable for 4H-SiC VDMOSFET.